Model Pendidikan Nilai Humanis Religius Pada Madrasah Aliyah di Kabupaten Nunukan - Fitriono, Eko Nani; Nur Qoria B.; Suharmin Saqban; Febri Cahyanti; Ramdani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to examine the model of religious humanistic education values applied in Madrasah Aliyah in Nunukan Regency, by conducting mapping involving three Madrasah Aliyah, namely Madrasah Aliyah Al-Anshari Nunukan, Madrasah Aliyah Ma’arif NU 01 Nunukan Selatan, and Madrasah Aliyah Al-Khairaat Nunukan. There are five main reasons underlying the research on the model of religious humanistic education values in these Madrasah Aliyah. First, the socio-cultural diversity in Nunukan that requires value education to build social harmony. Second, the influence of globalization that threatens the morals of teenagers, necessitating strengthening character based on religious humanistic values. Third, the strategic role of madrasah in shaping noble character and reinforcing Islamic identity. Fourth, the local context of Nunukan as a border area facing the influence of foreign cultures. Fifth, the crisis of values among teenagers, such as low tolerance, responsibility, and social concern. Data was collected through in-depth interviews with the Headmaster and teachers of the three Madrasah Aliyah in Nunukan Regency. The main focus of this research is to understand how the model of religious humanist education is implemented in Madrasah Aliyah in Nunukan Regency, to analyze educational strategies for internalizing religious humanist values in Madrasah Aliyah in Nunukan Regency, and to determine the implications of implementing the model of religious humanist education in Madrasah Aliyah in Nunukan Regency.